Aportes a la interculturalidad por parte de los kichwa hablantes de la carrera de Comunicación. - Calvopiña Zurita, Juan Diego (2020)
The Kichwa, is one of the mother tongues recognized in the Constitution of Ecuador, is a tool for communication and identity construction of communities and people. Specifically in the field of communication, language, as a system of signs, buildings and intercultural products. In Ecuador, there is a part of its population that uses Kichwa and Spanish to express their ideas and thoughts; This population segment has always felt relegated in terms of equal opportunities, it is here that the contribution that the academy provides in the teaching of their native language becomes decisive, as well as developing other tools that give them the opportunity to spread their knowledge; then the Faculty of Communication of the Technical University of Cotopaxi becomes a fundamental piece to be the entity that develops communication products in which they consider the use of the Kichwa and Spanish language as fundamental axes of an intercultural contribution. The research project achieves through the mixed methodology, qualitative quantitative propose intercultural communication products that can be implemented in the journalism club, on the radio or in other digital media; in order to strengthen the cultural identity of the Communication career in Cotopaxi and provide the referred products to the population that in more than 20% of its citizens are indigenous.